Characterization, identification and antibiogram studies of endophytic bacteria from cowpea [Vigna unguiculata (L.) Walp] - Marzan, LW; Alam, R; Hossain, MA (Bangladesh Journal of Agricultural Research, 2018)
This study included isolation, characterization and identification of endophytic bacteria from cowpea [Vigna unguiculata (L.) Walp] roots from Hathazari upazilla, Chittagong, Bangladesh and three specis of bacteria, Staphylococcus intermedius, Staphylococcus caprae and Staphylococcus saprophyticus were finally identified based on their morphological and biochemical characteristics according to established protocol. Results of antibiotic sensitivity pattern of those endophytic bacteria suggested that they can be utilized as a cost-effective biological control agent in future applications, such as delivery of enzymes for controlling certain plant diseases against various pathogens. The findings of this study may help to determine the potential application of those endophytic bacteria in biotechnology, medicine and agriculture. Bangladesh J. Agril. Res. 43(2): 175-186, June 2018